The dynamics between technological support, work-life balance, and Islamic leaders’ productivity in Indonesia (International Journal of Management and Sustainability, 2025)
This study examines the dynamic between technological support, work-life balance, and Islamic leaders productivity in Indonesia. Productivity is a core expectation in religious teachings and governmental policies, yet many nations with Islamic identities face challenges in achieving high workplace productivity. The widespread issue of mismanagement in Muslim-majority countries contrasts sharply with Islamic principles, which advocate for efficiency and excellence. This study explores how technology can enhance the work-life balance of Muslim leaders and, consequently, improve their productivity. The study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) and an exploratory approach to look at 256 responses from business leaders in Indonesia who say they are Muslim. The findings support the hypothesis that strategic use of technology can positively influence productivity by mediating the balance between professional and personal responsibilities. Additionally, self-efficacy is examined as a moderating factor in the relationship between technological support and work-life balance, with results aligning with this proposition. The study highlights how Muslim leaders can leverage technology to manage their companies effectively while fulfilling religious obligations and maintaining household duties. However, the research also cautions against over-reliance on technology, as its potential negative impacts could threaten the delicate balance between work and personal life. Thus, thoughtful technological integration is essential to fostering sustainable productivity for Muslim leaders in the workplace management and personal needs.